Mental Health Assistant Chatbot For University Students Based On The Depression Anxiety And Stress Scale 21 (Dass-21) - Voon, Viola Li Wei (Universiti Malaysia Sarawak (UNIMAS), 2023)
Mental illness is becoming more common nowadays, particularly among university students. This is owing to the changing nature of society today, which may cause stress on society members, as well as the COVID-19 pandemic, which causes a global lockdown. Furthermore, relationship problems may contribute to mental illness among university students. The lingering effects of this condition may result in untreated mental disease that may even lead to suicidal thoughts. The proposed solution is a Mental Health Assistant Chatbot that can provide a psychometric evaluation by using Depression Anxiety and Stress Scale 21. (DASS21). Through comprehensive testing involving users and practitioners, the chatbot prototype demonstrated effectiveness in supporting mental health prevention. Feedback from practitioners affirmed its usefulness in their practice. The study involved 15 university students, with the majority being male (60.0%) and in the age range of 24-26 years (53.3%). While most students agreed with the chatbot's features, some aspects such as information availability (6.67%) and user interface design were rated as (13.33%) average, suggesting a need for improvement in knowledge, data, and functionality. By addressing these limitations and receiving positive feedback, our study contributes to enhancing mental health support through technology.